PROSES PERENCANAAN DAN PENYELENGGARAAN EVENT AMCC 2023 OLEH PT HYPE IDEA - Putri, Riza Annisa (Bisnis Event, 2025)
The 2023 Astra Motor Champion Club (AMCC) event is included in the corporate event category with the type of event being an award ceremony. The event was held to provide motivation to employees to improve their performance professionally. The purpose of this research is to determine the process of planning and organizing the 2023 Astra Motor Champion Club (AMCC) event. This research uses a qualitative descriptive approach data analysis method with data collection methods in the form of interviews conducted with the project officer as the main role in the entire series of events, then the observation method to observe during the planning process to the implementation of the event, and the documentation method as evidence of information during the activity in the form of images. The research results show that in the planning process there is a registration preparation stage, namely the data collection stage. These stages consist of receiving the participant database, creating a sample participant QR Code, testing the participant's QR Code, creating all participant QR Codes, creating an AMCC 2023 invitation design, and uploading it to Google Drive. Apart from that, in the process of organizing the event there are two processes, namely controlling the participant registration process and the mobile implementation of the awards session.